2,3-Butanedione monoxime attenuates the β-adrenergic response of the L-type Ca2+ current in rat ventricular cardiomyocytes - Julio Alvarez-Collazo; Ana Iris López-Medina; Loipa Galán-Martínez; Julio L. Alvarez (Journal of Pharmacy & Pharmacognosy Research, 2016)
Context: 2,3-Butanedione monoxime (BDM), an uncoupler of cardiac contraction, is commonly used in enzymatic dissociations to prevent hypercontraction of cardiomyocytes and in cardioplegic solutions to decrease oxygen demand during surgery. However, BDM affects multiple cellular systems including the L-type Ca2+ current (ICaL). If its phosphatase activity is the mechanism underlying the decrease ICaL in cardiomyocytes is a still unresolved question.